Genetic parameters and factors affecting reproductive performance in White Fulani cattle in southern Nigeria - Mrode, Raphael A.; Akinokun, J.O. (Springer, 1986)
Data on reproductive performance of the White Fulani (Bunaji) cattle in Southern Nigeria were analysed. Age at first calving, first and overall calving intervals averaged 4.03± 0.43 years, 436.19±9.32 and 420.98± 4.11 days respectively. The year of birth significantly affected age at first calving and calving interval (P < 0.01) but the season of birth had significant effect only on calving interval (P < 0.05). In addition the age of the dam also affected the calving interval (P < 0.05) but the sex of the calf nursed had no effect. Heritability estimates from half-sib analysis were 0.01± 0.03, 0.26±0.10 and 0.28±0.08 respectively for age at first calving, first and overall calving intervals. Low repeatability estimates were obtained for calving intervals.